2020
DOI: 10.1038/s41467-020-16380-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct transfer of tri- and di-fluoroethanol units enabled by radical activation of organosilicon reagents

Abstract: Trifluoroethanol and difluoroethanol units are important motifs in bioactive molecules, but the methods to direct incorporate these units are limited. Herein, we report two organosilicon reagents for the transfer of trifluoroethanol and difluoroethanol units into molecules. Through intramolecular C-Si bond activation by alkoxyl radicals, these reagents were applied in allylation, alkylation and alkenylation reactions, enabling efficient synthesis of various tri(di) fluoromethyl group substituted alcohols. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Manganese­(III) is widely applied as a one-electron-transfer oxidant in organic synthesis to furnish C–C, C–O, or C–P couplings. In our previous work, we have found that with the combination of 1,1,1,3,3,3-Hexafluoroisopropanol (HFIP) and Mn­(OAc) 3 ·2H 2 O, several C–S bonds can been successfully constructed even at room temperature, which cannot be achieved in other solvent systems. This is probably owing to the unique solvent effects of HFIP, leading to the stabilization of radical intermediates and high-valence metal centers . In our efforts toward developing novel methods for installing sulfonyl moiety into molecules, we occasionally identified a sulfonated product instead of the expected sulfinate or sulfone. , Herein, we present preliminary results of this unexpected Mn­(OAc) 3 ·2H 2 O-promoted direct aromatic sulfonation with K 2 S 2 O 5 (Figure C).…”
Section: Introductionmentioning
confidence: 99%
“…Manganese­(III) is widely applied as a one-electron-transfer oxidant in organic synthesis to furnish C–C, C–O, or C–P couplings. In our previous work, we have found that with the combination of 1,1,1,3,3,3-Hexafluoroisopropanol (HFIP) and Mn­(OAc) 3 ·2H 2 O, several C–S bonds can been successfully constructed even at room temperature, which cannot be achieved in other solvent systems. This is probably owing to the unique solvent effects of HFIP, leading to the stabilization of radical intermediates and high-valence metal centers . In our efforts toward developing novel methods for installing sulfonyl moiety into molecules, we occasionally identified a sulfonated product instead of the expected sulfinate or sulfone. , Herein, we present preliminary results of this unexpected Mn­(OAc) 3 ·2H 2 O-promoted direct aromatic sulfonation with K 2 S 2 O 5 (Figure C).…”
Section: Introductionmentioning
confidence: 99%
“…Its recent application in organic synthesis has demonstrated substantial interest and demand for this transformation. 7 However, the narrow derivatization scope of 2-carboxyallyl sulfone limits its application. Owing to the synthetic limitation in introducing substituents at the α-sulfonyl position, 8 it effectively allows substitution only at the alkene terminus; this substitution pattern tends to hinder radical alkene-insertion reactions.…”
mentioning
confidence: 99%
“…Another useful reaction is the stereoselective in situ oxidation of the chiral allylboron compounds to the corresponding α-CF 3 allylic alcohols 8a−c (Figure 3c), which were obtained in 50−78% yield with 90−99% ee. The corresponding trifluoroethanol motif 49,50 occurs for example in antitumor agent Z 28 and the monoamine oxidase inhibitor befloxatone (Figure 1d). 29 The asymmetric homologation concept can also be extended to the synthesis of chiral α-silyl allylboronic acids, such as 1h-OEt (Figure 3d).…”
mentioning
confidence: 99%